Евгений Онегин: [роман в стихах] / Александр Пушкин - Пушкин Александр Сергеевич (Эксмо, 2008)
Экземпляры: Аб (20081203) / Инвентарный номер: 93055 / Цена: 75.00 / Авт.знак: П 91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1